Current Challenges and Opportunities in Non-native Chemical Production by Engineered Yeasts - Kim, Jiwon; Hoang Nguyen Tran, Phuong; Lee, Sun-Mi (Frontiers in Bioengineering and Biotechnology, 2020)
Yeasts are promising industrial hosts for sustainable production of fuels and chemicals. Apart from efficient bioethanol production, yeasts have recently demonstrated their potential for biodiesel production from renewable resources. The fuel-oriented product profiles of yeasts are now expanding to include non-native chemicals with the advances in synthetic biology. In this review, current challenges and opportunities in yeast engineering for sustainable production of non-native chemicals will be discussed, with a focus on the comparative evaluation of a bioethanol-producing Saccharomyces cerevisiae strain and a biodiesel-producing Yarrowia lipolytica strain. Synthetic pathways diverging from the distinctive cellular metabolism of these yeasts guide future directions for product-specific engineering strategies for the sustainable production of non-native chemicals on an industrial scale.